Influence of the Madden‐Julian Oscillation on Continental United States Hurricane Landfalls. Issue 7 (30th March 2023) - Klotzbach, Philip J.; Schreck, Carl J.; Compo, Gilbert P.; Wood, Kimberly M.; Oliver, Eric C. J.; Bowen, Steven G.; Bell, Michael M.
Abstract: The Madden‐Julian oscillation (MJO) significantly impacts North Atlantic hurricanes, with increased hurricane activity occurring when the MJO enhances convection over Africa and the tropical Indian Ocean and suppressed hurricane activity occurring when the MJO enhances convection over the tropical Pacific. Using data from 1905 to 2015, we find more tropical cyclones (TCs) make landfall in the continental United States when the MJO enhances tropical Indian Ocean convection. In addition, when the MJO enhances Western Pacific and Western Hemisphere convection, TC activity is preferentially favored in the Caribbean, leading to more Gulf Coast landfalls. As MJO‐enhanced convection moves to the Indian Ocean and Maritime Continent, more storms form in the tropical Atlantic, favoring Florida Peninsula and East Coast landfalls. The MJO's TC steering wind modulation appears to be secondary to its genesis location modulation. Plain Language Summary: The Madden‐Julian oscillation (MJO) is a large‐scale atmospheric signal of winds, rainfall, and surface pressure along the equator that circles the globe every 30–70 days. The MJO's location affects wind patterns that can then increase or decrease North Atlantic hurricane activity. When the MJO increases thunderstorms (convection) over Africa and the Indian Ocean, there tend to be more North Atlantic hurricanes. We show that the MJO patterns that increase North Atlantic hurricane activity also make hurricane landfalls more likely in the continental United States. We are likely to see more landfalls from Texas to the Florida Panhandle than from the Florida Peninsula to Maine when the MJO increases thunderstorms over the Western Pacific and Western Hemisphere. Landfalls from the Florida Peninsula to Maine tend to increase compared with Texas to Florida Panhandle landfalls when the MJO increases thunderstorms over the Indian Ocean. We believe this shift in landfall location is related to where the MJO helps storms form and less related to how the storms move after they form. Key Points: The Madden‐Julian oscillation (MJO) significantly impacts continental US hurricane landfall frequency Gulf Coast hurricane landfalls are favored when the MJO is enhancing Western Pacific/Western Hemisphere convection East Coast hurricane landfalls are favored when the MJO is enhancing Indian Ocean/Maritime Continent convection